A new approach for crack detection in plate structures using an integrated extended finite element and enhanced vibrating particles system optimization methods. (February 2021) - Fathi, Hamed; Hoseini Vaez, S.R.; Zhang, Qianyun; Alavi, Amir H.
Abstract: This study presents a new geometry-based crack detection approach for plate structures based on the integration of a dynamic extended finite element method (XFEM) and a physics-based optimization algorithm called enhanced vibrating particles system (EVPS). The so-called XFEM-EVPS method is applied to solve a forward problem. The problem is unraveled by applying traction loading phases and capturing environmental responses in two dimensions in each phase. Then, the EVPS algorithm is deployed to solve the inverse problem. The studied plate structures are analyzed by means of both fine and coarse meshing. Furthermore, each dissolved problem is similarly investigated through applying noise. The results indicate the efficiency of the proposed XFEM-EVPS method in detecting crack location. A comparative study is further conducted to benchmark the performance of the XFEM-EVPS method against a hybrid XFEM and particle swarm optimization approach.